Constant temperature induced stresses in evacuated enclosures for high performance flat plate solar thermal collectors. (April 2016) - Henshall, Paul; Eames, Philip; Arya, Farid; Hyde, Trevor; Moss, Roger; Shire, Stan
Highlights: We describe the basic components of evacuated flat plate solar thermal collectors. Enclosure glass cover safety limits defined as function of pillar array parameters. Finite element method simulations compared to experimental strain measurements. Suitable selection of design parameters ensures collector enclosure survivability. Abstract: A flat-plate solar thermal collector's efficiency can be much improved if the enclosure in which the solar absorber is housed can be evacuated. This would result in a high performance, architecturally versatile solar thermal collector capable of supplying clean energy efficiently for use in applications including residential hot water and space heating. This paper focuses on the design of evacuated enclosures for flat-plate solar collectors, in which the solar absorber is completely surrounded by a thin layer (4–10 mm) of thermally insulating vacuum, resulting in a thin solar thermal collector (depth < 20 mm). The expectations, requirements and applications of these solar collectors are discussed along with a description of the enclosure concept under consideration. Potential seal materials are identified and their limitations examined. Finite element modelling results are presented of a study investigating how the glass cover of such enclosures are mechanically stressed when subject to atmospheric pressure loading and differential thermal expansion of dissimilar components. Finite element model predictions are validated against preliminary experimental strain measurements for existing experimental enclosures. It is demonstrated that with a suitably low temperature sealing process vacuum the designed enclosure can successfully withstand imposed stresses.